Armed with expertise : the militarization of American social research during the Cold War - Rohde, Joy, 1977- (American institutions and society., 2013)
This title shows how the social sciences became enmeshed in a militarized system that has persisted, even grown, in recent years as it moved off campus, making it less visible and therefore less controversial. Rohde offers especially striking and disturbing material on the blow-back of social science collaboration with the armed forces, as individuals and institutions moved beyond addressing threats abroad into assessing domestic disorder and attempting to control it.